2012
DOI: 10.2174/157016212803306023
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse, HIV-1 and Hepatitis

Abstract: During the course of human immunodeficiency virus type 1 (HIV-1) disease, the virus has been shown to effectively escape the immune response with the subsequent establishment of latent viral reservoirs in specific cell populations within the peripheral blood (PB) and associated lymphoid tissues, bone marrow (BM), brain, and potentially other end organs. HIV-1, along with hepatitis B and C viruses (HBV and HCV), are known to share similar routes of transmission, including intravenous drug use, blood transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 155 publications
1
25
0
1
Order By: Relevance
“…Coinfection with HIV is extremely common, with some 90% of HIVpositive PWID also living with HCV (Vickerman et al, 2013). HIV infection accelerates HCV disease progression, increasing risk for cirrhosis twenty-fold and for hepatocellular carcinoma by a factor of five (Parikh et al, 2012).…”
Section: Hcv Burden Treatment Efficacy and Availabilitymentioning
confidence: 99%
“…Coinfection with HIV is extremely common, with some 90% of HIVpositive PWID also living with HCV (Vickerman et al, 2013). HIV infection accelerates HCV disease progression, increasing risk for cirrhosis twenty-fold and for hepatocellular carcinoma by a factor of five (Parikh et al, 2012).…”
Section: Hcv Burden Treatment Efficacy and Availabilitymentioning
confidence: 99%
“…Liver disease has emerged as a common cause of death in HIV infected persons, with liver-related mortality closely associated with Hepatitis C virus (HCV) co-infection (Prakash, Mason, Luftig, & Bautista, 2002). An estimated four to five million people in the world are living with HIV-HCV co-infection (Parikh et al, 2012). Furthermore, the hepatotoxicity of antiretroviral therapy (ART) and substance use places added strain on the liver with the potential to exacerbate organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…Within the United States, from the approximate 1.2 million HIV-1-infected individuals, about 25% of these are co-infected with HCV [39]. The interplay between both the viruses is complex and usually leads to accelerated forms of HIV-1 disease as well as HCV disease [21]. In fact, some recent reports have suggested that HCV-related deaths are greater than HIV-1-related deaths in the United States, and that the HIV-1/HCV co-infected individuals are the ones bearing a significant portion of the mortality [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the varied immune response during HIV-1 and HCV infections as well as modulation of certain cytokines and chemokines such as IFN-γ, MCP-3, and MIP-3α, are significant factors in the altered pathogenesis of HIV-1 and HCV coinfection [20,21]. In a decade long study comparing HIV-1 mono-infected individuals versus HIV-1 and HCV co-infected individuals, the coinfected individuals showed an increased prevalence of multiple neurologic disorders, 60% in the co-infected individuals as compared to the 46% in the HIV-1 mono-infected individuals.…”
Section: Introductionmentioning
confidence: 99%